Faktor Penyebab Dan Upaya Penanggulangan Kekerasan Yang Dilakukan Oleh Prajurit Tentara Nasional Indonesia Angkatan Darat Kodim 1603 Sikka - Durang, Agustina; Medan, Karolus Kopong (Law Faculty, Nusa Cendana University, 2024)
Criminal acts develop ini various types, among which are violence or persecution. Apart from the types as fo the perpetrator, it is not only a civilian but can be done by the Indonesian National Army. In this study, the main issue are: (1) What are the factors that cause Army soldiers of Kodim 1603 Sikka to commit violence? (2) what efforts can be made by law enforcement to overcome violence committed by Army Soldiers of Kodim 1603 Sikka? The purpose of this study is to find out and explain the factors that cause violence committed by soldiers of Army Kodim 1603 Sikka and to know and explain the efforts that law enforcement can make to overcome violence committed by Army Soldiers Of Kodim 1603 Sikka. This type of of research is empirical juridical by looking directly at the field. The result showed that: (1) factors causing soldiers Kodim 1603 Sikka to commit violence, namely Internal Factors inculding ego factors, morality factors and weak legal awareness factors. External Factors include target or target factors, weak factors at that time and the role of victims. (2) Efforts made by Kodim 1603 Sikka overcome violence committed by soldiers Kodim 1603 Sikka: (a) Preemptive efforts by conducting socialization to members. (b) Preventim efforts by carrying out routine Jamdan and conducting legal counseling. (c) Repressive efforts are by taking legal action. The author’s suggestion is that there needs to be increased control, law enfocement and supervision from superiors within the unit and outside the unit.